0191 Developing The Knowledge, Skills And Behaviours For The Healthcare Teams Across The North West. (1st November 2014) - Hellaby, Mark; MacKinnon, Ralph
Abstract : Background: It has been recognised for the need to include human factors based training for students, trainees and as part of continuing professional development (NQB, 2013). The NWSEN has encouraged and developed region wide resources in a variety of setting to increase the awareness, uptake and develop skills in human factors. Description: This has included e-learning resources, inclusion of human factors within simulation faculty development, developing a regional scenario library including scenarios with human factor learning outcomes, assisting in the development of in-situ drills, regional audits, communicating the potential of simulation to leads of organisations and working with partners from other high risk industries. These resources have been used in a variety of setting including secondary healthcare, mental health and general practice. Potential impact: Evaluation of the various initiatives have indicated an increase in the awareness of human factor priniciples. Aditionally there has been an indication that individuals feel that the training has impacted positively on their clinical practice. Reference: NQB (2013) Human Factors in healthcare A concordat from the National Quality Board. Retrieved from http://www.england.nhs.uk/wp-content/uploads/2013/11/nqb-hum-fact-concord.pdf